2018
DOI: 10.1039/c8cp01274a
|View full text |Cite
|
Sign up to set email alerts
|

Vibrations of the p-chlorofluorobenzene cation

Abstract: The vibrations of the ground state cation (X[combining tilde]2B1) of para-chlorofluorobenzene (pClFB) have been investigated using zero-electron-kinetic-energy (ZEKE) spectroscopy. ZEKE spectra were recorded using different vibrational levels of the S1 state as intermediate levels, for which assignments were put forward in an earlier paper [W. D. Tuttle, A. M. Gardner, and T. G. Wright, Chem. Phys. Lett., 2017, 684, 339]. These different intermediate levels dramatically modify the Franck-Condon factors for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 42 publications
(87 reference statements)
3
11
0
Order By: Relevance
“…6, it can be inferred from the vertical intercept that the AIP is 72937±8 cm −1 ((9.0428±0.0010) eV). The measured value agrees fairly well with the previously reported one [23]. agree with previously reported values of 373, 782, 821 and 1176 cm −1 , which are allocated to modes 7b 1 , 10a 1 , 10b 1 and 18a 1 .…”
Section: E Spectra Of P-clfph Cationsupporting
confidence: 93%
See 1 more Smart Citation
“…6, it can be inferred from the vertical intercept that the AIP is 72937±8 cm −1 ((9.0428±0.0010) eV). The measured value agrees fairly well with the previously reported one [23]. agree with previously reported values of 373, 782, 821 and 1176 cm −1 , which are allocated to modes 7b 1 , 10a 1 , 10b 1 and 18a 1 .…”
Section: E Spectra Of P-clfph Cationsupporting
confidence: 93%
“…The adiabatic ionization potential (AIP) of p-ClFPh was 9.011±0.008 eV, which was reported through the equilibrium measurement method in 1978 [22]. In addition, Kemp et al reported AIP of p-ClFPh as 9.0408±0.0006 eV and analyzed the vibrational structures in ZEKE spectra [23]. In the same year, our group reported the vibrations of meta-bromofluorobenzene in the first excited state (S 1 ) and the cationic ground state (D 0 ), also gave the adiabatic excited-state energy and AIP [24].…”
Section: Introductionmentioning
confidence: 95%
“…The 2D-LIF and DF spectra show evidence of weak cross activity between 11 1 and 14 2 , but this could simply be FC activity. We have previously concluded that these levels are close to coincident in the pClFB molecule, 46 but that there was no clear evidence of interaction from the ZEKE spectra reported therein. In pFT, we have seen herein that there is also little evidence for any significant interaction between these two levels, which is in agreement with the results of our ZEKE study.…”
Section: Final Remarks and Conclusionmentioning
confidence: 80%
“…As a consequence, we conclude that each of the three states, 11 1 , 29 1 and 14 2 are inherently 'bright', again in agreement with conclusions we have made in other work on pFT and related molecules. 8,15,33,46 We have previously discussed in depth 29 a feature that appears at S1+845 cm -1 and the interactions there were isolated to the 18 2 m 1 level, which allowed couplings to vibtor combinations involving m = 2. In so-doing, the mechanism opens up couplings between vibrations of different symmetry; such is also included in the vibtor coupling of the three lowest-wavenumber vibrations included in the model of GL.…”
Section: Final Remarks and Conclusionmentioning
confidence: 98%
“…significant FC factor and all other observed vibrations gain intensity from that vibration. [59][60][61][62] Hence, the high intensity of, for example, the vibration 18b 1 in the MATI spectrum via 6b 1 (this work: 6a 1 ) of anisole has to be a result of either a simultaneous excitation or a mixed vibration in the S 1 state.…”
Section: Discussionmentioning
confidence: 93%